(untitled) (UNWE Yearbook, 2024)
We are living in times of big changes and unprecedented challenges in all sectors - from business, industry, healthcare, and politics to academia. Young people need to be equipped with knowledge, skills, and the right attitudes to be fully capable of participating and contributing to their societies. As a result of this 21 century has brought new challenges to educators. The article provides an insight into the roles relevant to today’s English language teachers.